Asymmetric Domain Nucleation from Dislocation Core in Barium Titanate: Molecular Dynamics Simulation Using Machine-Learning Potential through Active Learning - Deguchi, Genki; Kobayashi, Ryo; Azuma, Hikaru; Ogata, Shuji; Uranagase, Masayuki; Spreafico, Samuele (Physica Status Solidi-Rapid Research Letters, 2023)
Barium titanate (BaTiO3) is a ferroelectric material without toxic elements, whose ferroelectric properties such as permittivity, coercive field, and spontaneous polarization are affected by the nucleation of domains of reversed polarization and the motion of domain walls. Dislocations can act as obstacles to domain-wall migration or as active sites for domain nucleation. Thus, studies are conducted on the utilization of dislocations to improve the ferroelectric properties of BaTiO3. However, the atomistic mechanism of domain nucleation around the dislocation core is still unclear. In this article, a machine learning (ML) potential is developed to study the influence of dislocations on domain nucleation. The potential is trained using an active-learning approach to ensure accuracy in the bulk properties of the ferroelectric and paraelectric phases, as well as in the dislocation core structures in BaTiO3. Molecular dynamics simulations using the ML potential show that the influence of dislocations on polarization reversal depends on the directional relationship between the external electric field and the dislocation. Furthermore, strong local polarizations exist surrounding the dislocation core, owing to vacancies in the core. These polarizations can act as both domain nucleation sites and obstacles for domain migration when ordered along the dislocation line.
CRIS-Team Scopus Importer:2023-10-20
Keywords: BaTiO; dislocations; domain nucleations; machine-learning potentials

In situ temperature-dependent X-ray diffraction study of ferroelectric single crystal BCZT - Gadelmawla, Ahmed; Spreafico, Samuele; Heinemann, Frank Wilhelm; Liu, Donglin; Li, Qiang; Yan, Qingfeng; Hayashi, Koichi; Meyer, Benedikt; Webber, Kyle Grant (Acta Crystallographica Section A : Foundations and Advances, 2022)
Perovskite ferroelectrics (ABO3) are enabling components in numerous technological fields, including energy harvesting and storage and electromechanical transducer applications [1]. Among others, lead-free piezoelectric compositions based on Ba1-x(Zr0.2Ti0.8)O3-x(Ba0.7Ca0.3)TiO3 (BCZT) have shown promising electromechanical response that can match the currently used Pb(Zr,Ti)O3-based piezoelectrics [2]. To date, the average crystal structure has only been studied for polycrystalline BCZT, revealing rhombohedral (R3m), orthorhombic (Amm2), tetragonal (P4mm), and cubic (Pm m) phases in the 80–450 K temperature range [3–6]. Despite this, single crystal structure analysis is important, as it offers information about the crystal symmetry, phase transitions, static configurational displacement, and thermal vibration of each atom without the influence of grain structure. Although several previous studies have succeeded in growing BCZT single crystals [7–11], only Liu et al. have reported a high piezoelectric coefficient of 232 pC/N at room temperature for Ba0.798Ca0.202Zr0.006Ti0.994O3 single crystal that was grown with the spontaneous nucleation method [12]. The relatively high makes the crystal reported by Liu et al. the best candidate for structure investigation. In this study, and for the first time, in situ temperature-dependent single-crystal X-ray diffraction of lead-free ferroelectric perovskite BCZT is reported. The data were collected within the temperature range of 170–380 K, revealing rhombohedral (R3m), orthorhombic (Pmm2), and tetragonal (P4mm) crystal structures. In ferroelectric phases, both B-site and oxygen ions are displaced with respect to the A-site cations at their original position. This shift leads to spontaneous polarization in the crystal, which is the origin of ferroelectricity. Furthermore, the single crystal structure has been modelled via first-principles DFT simulations. The computational investigation aims to get an insight into the local atomic environment of the Zr and Ca dopants and the consequent spontaneous polarization (Ps). Few previous computational works on BCZT focus on the local atomic environment [13], and the non-stoichiometry makes it challenging to model this single crystal via discreet atom representation and periodic boundary conditions. As a fair compromise, we employed a 3x3x3 supercell featuring 135 atoms, where the fractional proportions are reproduced employing 21, 6, 26, and 1 atoms for Ba, Ca, Ti, and Zr elements, respectively. Starting from pure BaTiO3, we first introduced the single Zr atom in the Ti sublattice and, consequently, the 6 Ca atoms in the Ba sublattice, isolating and studying the contributions of the two dopants. The structural impact of Zr and Ca atoms is studied by looking at the distance between them and the neighbouring atoms. Whereas the introduction of Zr atom leads to an expected structural expansion, the arrangements of Ca atoms had to be sampled because they play a discriminating role in the relaxation process. Ultimately, the Ps is evaluated via Berry Phase calculations and Born Effective Charges applied on the atomic displacements derived by computational and experimental structures. The adoption of multiple methods provides us clarity around the gray-zone of the evaluation of this property.

Investigation of ferroelectric Ba1−xCaxZryTi1−yO3 single crystal by in situ temperature-dependent x-ray diffraction and first-principles calculations - Gadelmawla, Ahmed; Spreafico, Samuele; Heinemann, Frank Wilhelm; Urushihara, Daisuke; Liu, Donglin; Li, Qiang; Yan, Qingfeng; Ceresoli, Davide; Kimura, Koji; Hayashi, Kouichi; Meyer, Bernd; Webber, Kyle Grant (Journal of Applied Physics, 2023)
In situ temperature-dependent crystal structure of lead-free ferroelectric perovskite Ba0.798Ca0.202Zr0.006Ti0.994O3 single crystal was characterized using x-ray diffraction from 170 to 380 K. Three phases were identified at different temperatures of 170, 220, and 298 K, revealing rhombohedral (R3m), orthorhombic (Pmm2), and tetragonal (P4mm) crystal structures, respectively. The change in the bond length and its distortion are reported for both AO12 and BO6 polyhedrons, allowing for the estimation of the spontaneous polarization. The Debye-Waller factor is reported as a function of temperature for A and B-sites. Density-functional theory calculations on the tetragonal phase were performed to obtain information on the distribution of the Ca ions, the local atomic displacements, and the ideal value of the spontaneous polarization of a defect-free crystal at 0 K. We find that Ca prefers to arrange in columnar 2D plates oriented along the tetragonal axis. The Ca ions avoid being next neighbors of Zr; however, the specific arrangement of Ca has only a minor impact on the spontaneous polarization.
CRIS-Team Scopus Importer:2023-11-03